2017
DOI: 10.1007/s10047-017-0975-4
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions after continuous flow left ventricular assist device implantation

Abstract: Continuous flow left ventricular assist device (CF-LVAD) therapy has improved the survival of patients with advanced heart failure. However, the readmission rate of CF-LVAD patients is still relatively high. A total of 90 patients who received CF-LVADs between April 2011 and March 2016 at our institute and were discharged home were analyzed retrospectively. They were followed up through March 2017. Clinical data, including frequency, length and etiology of readmission, were obtained from medical records. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The readmission frequency of 3.2 per patient-year in this study was slightly higher than that reported in previous studies. The mean time to first readmission was 57 days, which was longer than a previous report (Vidula et al, 2018) of 48 days but shorter than in a report by Kimura et al (2017). The readmission frequency differed between implanted HeartMate-II or HeartWare devise (Haglund et al, 2015) but was not different between destination therapy and bridge to transplantation LVAD recipients (Bradner et al, 2013).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The readmission frequency of 3.2 per patient-year in this study was slightly higher than that reported in previous studies. The mean time to first readmission was 57 days, which was longer than a previous report (Vidula et al, 2018) of 48 days but shorter than in a report by Kimura et al (2017). The readmission frequency differed between implanted HeartMate-II or HeartWare devise (Haglund et al, 2015) but was not different between destination therapy and bridge to transplantation LVAD recipients (Bradner et al, 2013).…”
Section: Discussionmentioning
confidence: 55%
“…Readmission rate or frequency is an important clinical outcome, and several studies (Kimura et al, 2017; Vidula et al, 2018) have reported the average readmission frequency range of 1.34–1.79 per patient-year after discharge. The readmission frequency of 3.2 per patient-year in this study was slightly higher than that reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of unplanned readmission was 1.7 per year in our cohort, consistent with the previously published data. [4,15,16] In addition, the frequency of readmissions reduced monotonically during follow-up, which indicates that LVAD therapy is associated with further recovery in overall medical profile of patients over time in this population.…”
Section: Discussionmentioning
confidence: 86%
“…[3] Previous reports have revealed that readmission rate is around 80% during follow-up, and most of them are unplanned. [4,5] Due to the rapid increase and diversification of this specific patient population, it is important to analyze the problems encountered in the outpatient setting.…”
mentioning
confidence: 99%
“…Multiple risk factors for stroke occurrence after LVAD implantation have been documented, including history of stroke, pre‐existing atrial fibrillation, diabetes mellitus, suboptimal anticoagulation regimens, hypertension, systemic infection, and aortic cross‐clamping with cardioplegic arrest . Regardless of etiology, postoperative stroke is an important cause of morbidity after LVAD implantation and can be a cause for hospital readmissions .…”
Section: Discussionmentioning
confidence: 99%